TRANSFORMASI PEMIKIRAN HARUN NASUTION: MENYONGSONG PENDIDIKAN ISLAM ABAD KE-21 - Ahmad Syahri Mubarok; Hasan Basri; Hilman Rizky Hasibuan (STIT Islamic Village Tangerang, 2023)
This research aims to determine the transformation of Harun Nasution's thinking in the context of Islamic education in the 21st century and determine the relevance of his thinking to Islamic education. The method used in this research is to use a type of library research. Library study is an activity for reading in the form of books, articles, dictionaries, or journals. The results of the research state that the renewal of Islamic education in Indonesia, namely: there is a renewal of the Indonesian Islamic higher education curriculum, a renewal of the academic traditions of Islamic higher education in Indonesia, the establishment of a postgraduate course at IAIN, the realization of the transformation of IAIN to UIN. Then, Harun Nasution's thoughts have high relevance in facing the challenges and opportunities of Islamic education in the 21st century. Its critical thinking and inclusiveness helps students develop analytical thinking skills and understand differences in an increasingly diverse society. In addition, an openness approach to change helps Islamic education adapt to changing times and technology.